2014
DOI: 10.1210/jc.2014-1802
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Infertility: Insights From in vitro Fertilization Cycles

Abstract: Vitamin D is an emerging factor influencing female fertility and IVF outcome. Additional studies are pressingly needed to confirm a causal relationship and to investigate the potential therapeutic benefits of vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 19 publications
5
79
0
8
Order By: Relevance
“…Recent reports have suggested that 25 hydroxyvitamin D ([25(OH)D]) was positively correlated with IVF pregnancy rate (Garbedian et al 2013, Paffoni et al 2014, Rudick et al 2014, whereas others found no significant association (Fabris et al 2014, Franasiak et al 2015, Abadia et al 2016. However, these studies were relatively small with between 100 and 150 participants in each deficient/ sufficient arms, and they defined different cut-off values for VitD insufficiency (<75 or <50 nmol/L), thus making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have suggested that 25 hydroxyvitamin D ([25(OH)D]) was positively correlated with IVF pregnancy rate (Garbedian et al 2013, Paffoni et al 2014, Rudick et al 2014, whereas others found no significant association (Fabris et al 2014, Franasiak et al 2015, Abadia et al 2016. However, these studies were relatively small with between 100 and 150 participants in each deficient/ sufficient arms, and they defined different cut-off values for VitD insufficiency (<75 or <50 nmol/L), thus making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the clinical pregnancy rates were 20% and 31%, respectively, with an adjusted odds ratio of 2.15 for clinical pregnancy in women with vitamin D >/-20 ng/ml. Furthermore, a subgroup analysis revealed that the group with the highest serum level of vitamin D (>30 ng/ml) resulted in the highest chances of pregnancy [85].…”
Section: Vitamin D and Reproductionmentioning
confidence: 98%
“…In vitro studies, it has been shown that vitamin D receptors are expressed in murine endometrium and ovary throughout the estrous cycle, whereas knockout experiments have shown that vitamin D receptor null mice experience uterine hypoplasia and impaired folliculogenesis [85].…”
Section: Vitamin D and Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that vitamin D is an emerging factor influencing female fertility and IVF outcome. 22 Women with sufficient levels of vitamin D are significantly more likely to achieve clinical pregnancy following IVF.…”
Section: Clinical Efficiency Of Vitamin D In Female Infertilitymentioning
confidence: 99%